Determining a Trusting Environment for Maternity Care: A Framework Based on Perspectives of Women, Communities, Service Providers, and Managers in Peri-Urban Kenya - Sripad, Pooja; Merritt, Maria W.; Kerrigan, Deanna; Abuya, Timothy; Ndwiga, Charity; Warren, Charlotte E. (Frontiers in Global Women's Health, 2022)
Trust in health service providers and facilities is integral to health systems accountability. Understanding determinants of trust, a relational construct, in maternity settings necessitates exploring hierarchical perspectives of users, providers, and influencers in the care environment. We used a theoretically driven qualitative approach to explore trust determinants in a maternity setting across patient-provider, inter-provider, and community-policymaker interactions and relationships in peri-urban Kenya. Focus groups (n=8, N=70) with women who recently gave birth (WRB), pregnant women, and male partners, and in-depth-interviews (n=33) with WRB, health care providers and managers, and community health workers (CHWs) were conducted in 2013, soon after the national government’s March 2013 introduction of a policy mandate for ‘Free Maternity Care’. We used thematic coding, memo writing, and cross-perspective triangulation to develop a multi-faceted trust determinants framework. We found that determinants of trust in a maternity setting can be broadly classified into six types of factors, where each type of factor represents a cluster of determinants that may each positively or negatively influence trust: patient, provider, health facility, community, accountability, and structural. Patient factors are prior experiences, perceived risks and harms, childbirth outcomes, and maternal health literacy. Provider factors are empathy and respect, responsiveness, and perceived capability of providers. Health facility factors are “good services’ as perceived by patients, physical environment, process navigability, provider collaboration and oversight, discrimination, and corruption. Community factors are facility reputation and history, information channels, and maternal health literacy. Accountability factors are alignment of actions with expectations, adaptations to policy changes, and voice and feedback. Structural factors are institutional hierarchies and policies in the form of professional codes. Trust determinants are complex, nuanced and reflect power dynamics across relationships. Findings offer insight into socio-political maternity norms and demand a more equitable care interface between users and providers.